Evaluation of Heavy Metals and Histopathology in O. nioloticus and C. gariepinus of Two Selected Corridors (Almakashi and Gwani) of River Gongola in Gombe State, Nigeria (Journal of Environmental Bioremediation and Toxicology, 2025)
Agricultural runoff, industrial effluents, and domestic waste are examples of anthropogenic stressors that contaminate freshwater. This is particularly applicable to Nigeria's Gongola River. This study examined the accumulation of heavy metals and histopathological alterations in Oreochromis niloticus and Clarias gariepinus from Almakashi, Gwani, and the reference site Balanga Dam. We quantified the concentrations of copper (Cu), cadmium (Cd), chromium (Cr), lead (Pb), nickel (Ni), arsenic (As), manganese (Mn), and iron (Fe) in the gills, liver, and kidneys. The gills of C. gariepinus from Almakashi exhibited the highest concentrations of Cu (17.20±1.17 µg/g), As (44.93±3.72 µg/g), and Ni (34.83±5.20 µg/g). The kidney tissues from Balanga exhibited the lowest concentrations of Fe (10.16±1.25 µg/g), Mn (1.10±0.20 µg/g), and Cu (4.23±0.30 µg/g) among O. niloticus tissues. Cadmium and lead concentrations were predominantly undetectable in kidney and liver tissues across all locations. Histopathological examination revealed that gill alterations (epithelial lifting, hyperplasia, fusion) were observed in O. niloticus from Almakashi in up to 100% of cases, while kidney necrosis was observed in C. gariepinus in up to 44.44% of cases. Steatosis (10–33.34%) and sinusoidal congestion (up to 14.29%) were among the hepatic lesions. Metal accumulation in Almakashi and Gwani was significantly greater than in Balanga Dam (p < 0.05). C. gariepinus typically exhibited elevated tissue concentrations, likely due to their consumption of benthic organisms. These findings validate that these species serve as effective bioindicators and underscore the need to rehabilitate the Gongola River and restore its ecosystems.
Keywords: Heavy metal accumulation; Oreochromis niloticus; Clarias gariepinus; Histopathology; Gongola River pollution